Rola Standardów Ochrony Małoletnich w systemie ochrony małoletnich. Analiza na przykładzie SOM wprowadzonych w poznańskich szkołach podstawowych - Appelt, Karolina (Studia Edukacyjne, 2026)
Research objective: determining the role of standards for the protection of minors (SOM) in the system of protection of minors based on an analysis of the content of documents that make up the standards of Poznan primary schools. An additional objective was to identify the so-called good practices in developing rules for the protection of minors and formulate recommendations for educational practice. The research problem and methods: to decide whether Poznań primary schools have complied with the statutory obligation to introduce standards for the protection of minors and what role SOM plays in the system of protection of minors. The research uses the analysis method of existing documents in the form of standards for protecting minors posted on institutions’ websites. The process of argumentation: The argumentation begins with an introduction indicating changes in the law, initiating work on developing and introducing standards for the protection of minors in the internal order of schools and other educational institutions. Then, the research methodology was outlined, and the results and general conclusions were presented. The next part of the argument reflects on constructing the student-teacher relationship based on the examined documents. Research results: schools fulfilled their obligation to develop and inform about the SOM in force in the institution. At the declarative level, the regulations contained in these internal acts have orderly, educational, and creative functions. The research also showed the specificity of student-teacher relations regulations. Conclusions, recommendations and applicable value of research: in the examined SOMs, the emphasis is placed on the normative dimension of regulations and their ordinal role. At the same time, the impact of education and upbringing is marginalized. Little attention paid to solutions based on interinstitutional cooperation. However, so-called good practices in this area are evident.